Outcome of Laparoscopic Deroofing of Renal Cyst- Our Experience (Medicine Today, 2019)
Introduction: To evaluate the outcome of laparoscopic deroofing of renal cyst for the management of symptomatic renal cyst.Materials & Methods: This study was performed on 32 patients having symptomatic renal cyst at the Department of Urology, Shahid Sheik Abu Naser Specialized Hospital, Khulna and two other private hospitals in Khulna from January 2015 to December 2017. Patients having cyst size less than 5cm, previous abdominal surgery and sepsis were excluded from this study. Transperitoneal approach was adopted in all cases. All patients were diagnosed by ultrasonography and computed tomography to determine the Bosniak classification of the cyst. Pain and cyst recurrence were assessed during the follow-up.Results: Thirty-two patients (mean age=52.9±12 years) with large renal cyst (mean size=35±13) were included. All procedures were completed successfully, with no major intraoperative complications. The mean (range) operative duration was 56 (35–125) min, affected by the site and number of cysts unroofed. All patients were symptom-free except one, who had a recurrent large cyst, anteriorly located, and who underwent open cyst deroofing.Conclusion: Laparoscopic deroofing of symptomatic renal cysts should be the standard of care, especially after failed percutaneous aspiration, with reduced postoperative pain, short hospital stay and cost effective. It is feasible with conventional laparoscopic instruments and gives a better cosmetic outcome.Medicine Today 2019 Vol.31(2): 114-116